Tracing the Culture of Science in the Islamic Tradition in Melayu-Nusantara (Islamization Offers in the Wan Nor Mohd Wan Daud Framework) - Mohammad Djaya Aji Bima Sakti; Muhammad Iqbal Fahlevi Ibnu Ahmad (al-Afkar, Journal For Islamic Studies, 2026)
This article analyzes the efforts to realize the discourse of the Islamization of Contemporary Science. The researcher explores Wan Daud's ideas on the intellectual and cultural traditions of Islamic science in the Malay-Nusantara archipelago by attempting to analyze the relevant Islamization framework to address the problems of globalization and secularization. The flow of globalization has the potential to obscure and shape the identity bias of a civilization. This runs in accordance with the spirit of Eurocentrism which has a truth-claim neutral attitude towards the nature of knowledge, but on the other hand, it actually strengthens the secularization process, thus impacting Western superiority. This problem is also felt by the Malay-Nusantara civilization. Currently, it faces significant challenges due to the influence of secularization and modernity under the heading of globalization, especially on aspects of culture and intellectual traditions. In this context, the idea of Islamization emerges as a potential solution to overcome the problems faced by Muslims in this century. Islamization consists of two main processes: self-liberation and self-return (devolution) to the natural nature of humanity which is their origin. Based on the above discourse on Islamization, the researcher observes that Wan Daud understands the context of Malay-Nusantara Islamization as a transformative effort encompassing various aspects, from theology and religious dogma to culture, thought, and civilization. This research observes that Wan Daud's framework emphasizes the liberation of reason and the restructuring of thought through language and science, with the ultimate goal of returning to one's natural state. Within this framework, Islamization is not merely viewed as a religious adaptation to modernity, but rather as an effort to renew and revitalize the intellectual culture of Muslims, making it a foundation for developing a just and civilized civilization in accordance with the teachings of the Qur'an and Sunnah.